2018
DOI: 10.20944/preprints201807.0008.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Membrane Active Peptides and Their Biophysical Characterization

Abstract: In the last 20 years, an increasing number of studies have been reported on membrane active peptides, which exert their biological activity by interacting with the cell membrane either to disrupt it and lead to cell lysis or to translocate through it to deliver cargos into the cell and reach their target. These peptides are attractive alternatives to currently used pharmaceuticals. Antimicrobial peptides (AMPs) and peptides designed for drug and gene delivery currently in the drug pipeline suggest that these m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 250 publications
(337 reference statements)
0
16
0
Order By: Relevance
“…MD simulations and modeling of membrane permeabilization rely on the assumption that permeabilization is an equilibrium process, a condition that is not always fulfilled, especially in the case of stochastic permeabilization [ 122 , 123 , 124 ]. The detection of such long processes [ 129 , 130 ] would require more advanced sampling algorithms including dual-resolution MD [ 131 ], coarse-grain simulations, steered MD [ 132 ], umbrella-sampling [ 133 , 134 ], metadynamics [ 135 , 136 ] or replica exchange, among others [ 130 , 137 , 138 , 139 ]. Our aim is to characterize the first steps of the interaction that are stationary on shorter timescales.…”
Section: Resultsmentioning
confidence: 99%
“…MD simulations and modeling of membrane permeabilization rely on the assumption that permeabilization is an equilibrium process, a condition that is not always fulfilled, especially in the case of stochastic permeabilization [ 122 , 123 , 124 ]. The detection of such long processes [ 129 , 130 ] would require more advanced sampling algorithms including dual-resolution MD [ 131 ], coarse-grain simulations, steered MD [ 132 ], umbrella-sampling [ 133 , 134 ], metadynamics [ 135 , 136 ] or replica exchange, among others [ 130 , 137 , 138 , 139 ]. Our aim is to characterize the first steps of the interaction that are stationary on shorter timescales.…”
Section: Resultsmentioning
confidence: 99%
“…Our slow exchange conditions therefore limit the value of k ex and k off to a maximum of 600 s −1 and the lifetime of the complex to a minimum of 1.7 milliseconds or much more, including the case of irreversible binding (the lifetime is the inverse of the off-rate constant). The detection of such long processes [ 74 , 75 ] would require more advanced sampling algorithms including dual-resolution MD [ 76 ], coarse-grain simulations, steered MD [ 77 ], umbrella-sampling [ 78 , 79 ], metadynamics [ 80 , 81 ], or replica exchange, among others [ 75 , 82 , 83 ]. This is beyond the scope of this work that aims at characterizing the steps at the very beginning of the interaction, in order to unravel the mode of action.…”
Section: Resultsmentioning
confidence: 99%
“…Peptides that interact with the plasma membrane through processes of traversal, fusion, or residing directly at the membrane surface interface are termed membrane active . It has been suggested that the manner in which the peptide locates within the membrane is highly dependent on the membrane lipid composition .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the manner in which the peptide locates within the membrane is highly dependent on the membrane lipid composition . Broadly categorized, the interactions have been described as the “barrel‐stave” and “carpet” mechanisms . The former process involves the insertion of the peptide into the membrane core while the latter involves binding at the surface primarily through interactions with the polar head groups.…”
Section: Introductionmentioning
confidence: 99%